2012
DOI: 10.1590/s1516-44462012000100016
|View full text |Cite
|
Sign up to set email alerts
|

A review on predictors of treatment outcome in social anxiety disorder

Abstract: Knowledge of various clinical and treatment features may help professionals to predict possible responses to therapeutic interventions in patients with SAD. However, given the diversity of measures used to assess response, further studies should be performed with standardized methods to investigate the aspects related to treatment resistance in SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…The degree of comorbidity remained a significant predictor of (more) symptom severity (LSAS score at treatment end) over and above the effects of symptom severity at the beginning of treatment (initial LSAS score); it also indicated a lower probability to achieve response (but not remission). As the variable ‘number of comorbid mental diagnoses’ combined other axis I and axis II diagnoses, this finding replicates in part some previous studies (Lincoln et al, ; Mululo et al, ). It is of note, however, that the incremental effects were rather small (see also Olatunji, Cisler & Tolin, ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The degree of comorbidity remained a significant predictor of (more) symptom severity (LSAS score at treatment end) over and above the effects of symptom severity at the beginning of treatment (initial LSAS score); it also indicated a lower probability to achieve response (but not remission). As the variable ‘number of comorbid mental diagnoses’ combined other axis I and axis II diagnoses, this finding replicates in part some previous studies (Lincoln et al, ; Mululo et al, ). It is of note, however, that the incremental effects were rather small (see also Olatunji, Cisler & Tolin, ).…”
Section: Discussionsupporting
confidence: 88%
“…The studies differ with respect to which variables were investigated. In the majority of studies, only a limited range of predictors was considered (refer to Lincoln et al, 2005 andMululo, De Menezes, Vigne, &Fontenelle, 2012 for overviews). Socio-demographic variables such as age, gender, marital status, education and occupation are typically unrelated to outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated predictors of outcome of psychological treatments for SAD (e.g., Craske et al, 2014; Mululo, Menezes, Vigne, & Fontenelle, 2012). However, only a few studies have identified baseline predictors of pharmacotherapy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse sentido, é correto afirmar que a ansiedade patológica está associada a baixos níveis de qualidade de vida, bem como a notórias deficiências sociais, educacionais e ocupacionais (MULULO et al, 2012). A desordem da ansiedade é considerada a doença mental mais comum em todo o mundo, sendo o diagnóstico psiquiátrico mais corrente em todo o globo, afligindo entre 10-30% da população (BADGUJAR;SURANA, 2010;NETTO et al, 2009).…”
Section: Resultsunclassified